Mix Marketing Strategy on The Business of Bosara Handicrafts in Bontonompo Selatan Gowa District - Anggi Angraeni; Hasnawi Haris; Aris Baharuddin (Jurnal Administrasi Bisnis, 2026)
This study examines the marketing mix strategy in the bosara handicraft product business in South Bontonompo, Gowa Regency. The purpose of this study was to determine the marketing mix strategy for the bosara handicraft product business in South Bontonompo, Gowa Regency, to determine the factors that influence the marketing strategy for the bosara handicraft product business in South Bontonompo, Gowa Regency. This research approach is quantitative. This research was carried outinSubdistrictSouth Bontonompo, Gowa Regency. Source of data in research isboss craftsmanin October to December 2022. Data collection techniques are in the form of observation, interviews and documentation. Data analysis techniques include data editing, data reduction, categorization, interpretation, data display, and drawing conclusions. The results showed that the marketing mix strategy for bosara handicrafts in South Bontonompo, Gowa Regency found that there were two types of bosara products produced, namely modern bosara products and traditional bosara products. The price for Bosara products is with the lowest price range of Rp. 200,000 up to the highest price of Rp. 1,000,000 which is the principal in determining the price is the raw material for production. Promotions carried out by craftsmen on average use offline and online sales on social media. The location of the craftsmen in the production and marketing of Bosara products is very strategic because the place for production and marketing is known by customers and easy to find. The factors of the marketing strategy for bosara handicrafts based on SWOT analysis in South Bontonompo, Gowa Regency found that the inhibiting factors resulted in thatthe production process carried out in the manufacture of bosara products and also the production tools used are still limited in their manufacture so that the production of making bosara products is limited. Supporting factors in the process of making a Bosara product business are family and environmental support which makes craftsmen more active in production and marketing in the field.